ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) PRODUCTIVITY POLICY APPROACH TO MEASURING CORPORATE INTEGRATED REPORTING AND CORE VALUES OF COMPANIES ON THE INDONESIA STOCK EXCHANGE - Susan Rachmawati; Andi Martias; Sudirja; Firstianty Wahyuhening F (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the dynamic relationship between the global Environmental, Social, and Governance (ESG) index and the Indonesian stock market , using data from the Indonesia Stock Exchange . ESG is an investment practice that considers environmental, social, and corporate governance impacts in investment decision-making. Thus, ESG is not only a priority for investors but also a crucial factor for companies seeking to attract new investors while maintaining the satisfaction of existing shareholders. In line with this objective, this study evaluates the effect of Corporate Integrated Reporting (CIR) on Core Value Company (CVC) disclosure in companies listed on the Indonesia Stock Exchange. The study sample includes 85 companies with available ESG scores for the period 2020 to 2025, along with annual report data for comparative analysis. Multiple regression methods are applied to assess the effect of ESG productivity policies on CVC within the context of integrated reporting. The results of the study show that CIR has a positive influence on CVC. In addition, ESG productivity policies are significantly associated with increased CIR benefits, although they do not have a direct impact on CVC. The results of this analysis emphasize the importance of implementing CIR and strengthening ESG productivity in enhancing a company's core value, as reflected in improved stock market performance. This research also indicates that advocacy for CIR and ESG disclosure can improve market efficiency, transparency, and corporate accountability